2022
DOI: 10.1186/s13034-022-00551-1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding youths’ concerns about climate change: a binational qualitative study of ecological burden and resilience

Abstract: Background Climate change has been shown to have long-term effects on mental health, yet, to date, there have been few studies on how children and adolescents experience and respond to ecological changes and how and why they engage in climate action. We explored empirically young people’s views about climate change and how distinct cultural contexts influence individual climate action. Methods We invited children and adolescents (ages 7 to 18) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…In this way, our effort has resulted in a virtual cycle of qualitative development. [44][45][46][47][48][49][50][51][52] We hope others will join us and create their own CoPs to support quality growth in CAP.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, our effort has resulted in a virtual cycle of qualitative development. [44][45][46][47][48][49][50][51][52] We hope others will join us and create their own CoPs to support quality growth in CAP.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Thomas et al (2022), participants who considered themselves activists seemed to be more prone to describing symptoms of anxiety, often after a turning point when they suddenly became aware of the climate crisis. Younger participants reported that they first encountered climate change information through online content, which sometimes increased their fears and sometimes soothed them (Thomas et al, 2022). Additionally Kelly (2017) concluded that those enrolled in environmental courses reported higher levels of anxiety and stress than those who did not attend, implying that awareness and knowledge of the environment contributed to their negative emotional state and distress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a global survey on climate anxiety among young individuals revealed higher levels of anxiety, negative emotions and future concerns than the countries already experiencing the effects of climate crisis (Hickman et al, 2021). In a study by Thomas et al (2022), participants who considered themselves activists seemed to be more prone to describing symptoms of anxiety, often after a turning point when they suddenly became aware of the climate crisis. Younger participants reported that they first encountered climate change information through online content, which sometimes increased their fears and sometimes soothed them (Thomas et al, 2022).…”
mentioning
confidence: 99%
“…Studies have demonstrated associations between rising temperatures and poor mental health outcomes, including suicide, hospital admission for mental health symptoms, and self-reported psychological distress (Lawrance et al, 2022). Beyond these disrupting events that compound negative social determinants of health, young people may have strong concerns about climate change, or “climate anxiety,” which includes an array of experiences or mental health symptoms (Thomas et al, 2022). In a 10-country survey of 10,000 youth and young adults, 84% of surveyed young people reported they were moderately, very, or extremely worried about climate change (Hickman et al, 2021).…”
Section: Social Determinants Of Health and Climate Concernsmentioning
confidence: 99%